Justice and negotiation. [article]. - Druckman, Daniel
This review article examines the literature regarding the role played by principles of justice in negotiation. Laboratory experiments and high-stakes-negotiations reveal that justice is complex concept, both in relation to attaining just outcomes and to establishing just processes. We focus on how justice preferences guide the process and outcome of negotiated exchanges. Focusing primarily on the two types of principles that have received the most attention, distributive justice (outcomes of negotiation) and procedural justice (process of negotiation), we introduce the topic by reviewing the most relevant experimental and field or archival research on the roles played by these justice principles in negotiation. A discussion of the methods used in these studies precedes a review organized in terms of a framework that highlights the concept of negotiating stages. We also develop hypotheses based on the existing literature to point the way forward for further research on this topic. -- (from the authors)